Nitrate supplementation and high-intensity performance in competitive cyclists - Hoon, M. W.; Hopkins, W. G.; Jones, A. M.; Martin, D. T.; Halson, S. L.; West, N. P.; Johnson, N. A.; Burke, L. M. (Applied Physiology, Nutrition, and Metabolism, 2014)
Consumption of inorganic nitrate (NO3-) is known to enhance endurance exercise performance in recreationally trained subjects. Here we report the effect on a high-intensity performance task in national-level cyclists. The performance test consisted of 2 cycle ergometer time trials of 4 min duration with 75 min between trials. In a randomized crossover design, 26 cyclists performed the test under the following 4 conditions (each separated by a 6-day washout): consumption of 70 mL of nitrate-rich beetroot juice at 150 min or 75 min before the first time trial, addition of a 35 mL "top-up dose" following the first time trial in the 150 min condition, and consumption of a placebo. A linear mixed model with adjustments for learning effects and athlete fitness (peak incremental power) was used to estimate effects on mean power, with probabilistic inferences based on a smallest important effect of 1.0%. Peak plasma nitrite (NO2-) concentration was greatest when nitrate was taken 75 min before the first time trial. Relative to placebo, the mean effect of all 3 nitrate treatments was unclear in the first time trial (1.3%, 90% confidence limits: ±1.7%), but possibly harmful in the second time trial (-0.3%, ±1.6%). Differences between nitrate treatments were unclear, as was the estimate of any consistent individual response to the treatments. Allowing for sampling uncertainty, the effect of nitrate on performance was less than previous studies. Under the conditions of our experiment, nitrate supplementation may be ineffective in facilitating high-intensity exercise in competitive athletes.